Expert-innovator behaviour questionnaire as a new tool for selecting potential experts - Deptuła Anna M.; Nosal Czesław S. (Engineering Management in Production and Services)
The effects of global change on development and the sustainability of the economy are visible in implementing innovations. Appropriate selection of experts, considering various knowledge areas, should use selected tools. The article introduces a research tool for selecting experts for innovation risk assessment. In particular, it aims to present individual measurement scales and their reliability assessment (Cronbach’s alpha). The article presents the factor structure of a potential expert’s competencies measured using a questionnaire. The questionnaire was developed for the appropriate selection of specialists from various industries, including production, mechanics, and management. The questionnaire constitutes a tool applicable for assessing and selecting people involved in the implementation and risk assessment of innovations. It is based on the following four scales (factors): open mind, closed mind, cognitive motivation, and response to uncertainty. The questionnaire’s effectiveness was studied using two research samples, n= 224 and n= 349, comprised of entrepreneurs and individuals professionally related to business and development and implementation of innovations. The interviewees were selected randomly. Factor analysis was used to reduce the test items in the questionnaire. The internal reliability of items was analysed using Cronbach’s alpha. The proposed questionnaire forms a new tool that can be used in selecting experts who deal with the risk assessment of innovations and in the broadly understood process of recruiting staff with appropriate competencies in terms of mindset characteristics. The article presents an analysis related to the conduct of typical research in Management and Quality Sciences, as well as practical principles guiding the use of the questionnaire, which may have wider application in the practice of risk management. The article presents the measurement tool with the answer key, which is a valuable guide for interpreting the results. The questionnaire facilitates the selection of individuals focused on independent and courageous problem-solving and the statement of evaluations. At the same time, an adequate level of caution should be respected, characterising people with risk aversion. Furthermore, creativity and openness are coupled with a considerable ability to develop new solutions and rationally respond to difficult and unpredictable situations.